Analysis of the Acceleration of Work Implementation with Additional Labor and Additional Working Hours using the Time Cost Trade Off Method (Case Study of the Grand Heaven Jakarta Funeral Home Elevator Extension Structure Development Project) - Ahmad Supriadi; Abdul Mubarok; Alip Prajoko; Retno Indriyati Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of construction work is sometimes not according to the predetermined plan, such as an increase in implementation time which results in the project being late, if there are signs of a delay in a work an alternative can be done immediately to speed up the time so that the project can be carried out as previously planned. The research carried out aims to analyze the optimum time and cost of the Grand Heaven Jakarta Funeral Home Elevator Extension Structure Development project after acceleration. This research implements the method through increasing the number of working hours and employees known as time cost trade off analysis or analysis of the exchange of time and costs. The procedure is through reducing the duration of work that has been planned previously which occupies the critical path section with the aim of obtaining benefits both in terms of cost and project time. This is intended to speed up the project completion time.